Effectiveness of botanical pesticides on Myzus persicae (Sulzer) and Aphis gossypii (Clover) (Hemiptera: Aphididae) in greenhouse pepper crops (Capsicum annuum L.) (2018)
A wide variety of arthropod pests that cause damage in agricultural crops can be found worldwide. The cotton aphids Aphis gossypii (Glover) and Myzus persicae (Sulzer) (Hemiptera: Aphididae) are the most significant arthropod pests, which affect greenhouse pepper crops. This research was carried out to determine the effectiveness of three distinct plant products used as an alternative biological aphid pest control in a greenhouse pepper crop in Concordia, Argentina. The effectiveness was determined by testing three formulas of essential plant oils or extracts, derived from cinnamon essential oil Cinnamomun verum (J. Presl.) [Cinnamon EO], Quassia essential oil Quassia amara (L.) [Quassia EO], neem oil Azadarichta indica (A. Juss.) [M neem] and garlic Allium sativum (L.) [M garlic]. It has to be noted that the latter two formulas contained other extracts/essential oils, which were compared to the absolute control (water). For that purpose, this research was carried out with a completely randomized design and replicated three times. The applications were made by means of a backpack sprayer, straight onto the foliage. The first application was made 1 week after the plant transplanting and afterward on a weekly basis until the end of the study. Subsequently, the total average number of aphids (adults and nymphs) on every leaf was recorded. The results showed that the treatment with neem oil (with M neem) recorded a lower number of aphids, as compared to the other treatments, including the absolute control. However, a significant number of parasitized aphids (mummies) were found on leaves treated with Quassia essential oil (Quassia EO).